Pengaruh Narasi dalam Konten Vlog Channel Youtube “Menjadi Manusia” Terhadap Sikap dalam Menjaga Kesehatan Mental - Fajar Hadi Saputra; Cholifah (Jurnal ISIP: Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
This article reports the results of research on the phenomenon of people with mental health disorder in the productive age group, which continues to increase. In an effort to overcome this phenomenon, there is the information about mental health that is packaged in narrative format in the “Menjadi Manusia” vlog on the YouTube channel. This study aims to measure the effect of the narrative in the vlog content on the narrative. transportation and people’s attitudes to maintaining the mental health. The theory used is the transportation. theory and the entertainment overcoming resistance model. The research method used is an explanatory survey with the subject of the vlog audience “Menjadi Manusia” who are chosen purposively. The results showed that story tellers and story receivers in the youtube vlog channel narration “Menjadi Manusia” had a positive effect on narrative transportation and narrative transportation had a positive effect on people’s attitudes in maintaining the mental health